Biodegradasi Anaerobik Makroalga Ulva sp. untuk Menghasilkan Biogas dengan Metode Batch - Krisye; Mujizat Kawaroe; Udin Hasanudin, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Anaerobic Biodegradation of Macroalgae Ulva sp. for Biogas Production with Batch Method. High carbohydrate and low lignin content of macroalgae Ulva sp. constitute their advantages as a potential substrate for biogas production. Biogas was generated through anaerobic biodegradation process using batch method. This study aimed to determine the potential of biogas and methane produced by Ulva sp. in a batch system. The research was conducted from December 2013 to July 2014 in the Laboratory of Surfactant and Bioenergy Research Centre (SBRC) of Bogor Agricultural Institute, Testing Laboratory of Agroindustry Technology Department of Bogor Agricultural Institute; and Agroindustrial Waste Management Laboratory of University of Lampung. The study started with proximate analysis, followed by manufacturing of cow dung starter, acclimatization process, and anaerobic biodegradation using the batch method. The result was analyzed using statistical program SPSS 17. Proximate analysis of Ulva sp. resulted in water content 16,7% , ash 14,9%, fat 2,9%, carbohydrates 60,3%, protein 5,3%, lignin 4,6%, total organic carbon 26,1%, nitrogen 1,3%, and C/N ratio 20,5. After acclimatization process, the biogas produced from 8.8 L of Ulva sp. biomass was 70.9 L with the pH ranged from 6.3 to 7.1, while anaerobic biodegradation process using batch method produced 153.9 L biogas with methane content of 51.1 L from 4 kg of Ulva sp. Form this research it is found that each kg of Ulva sp. is potential to produce 38.5 L of biogas with the methane content of 12.8 L. The correlation between COD and accumulated CH4 was -0,971.